2019
DOI: 10.3892/mmr.2019.10060
|View full text |Cite
|
Sign up to set email alerts
|

Renal dysfunction in a mouse model of GDM is prevented by metformin through MAPKs

Abstract: Gestational diabetes mellitus (GDM) incidence is increasing worldwide. In the present study, the effects of metformin on high fat diet (HFD)-induced renal dysfunction were investigated in GDM mice. In addition, the molecular mechanisms underlying metformin function were examined. GDM was induced by feeding pregnant mice a HFD, and mice were treated with two different doses of metformin (300 and 600 mg/kg/day) or PBS between embryonic day 11.5 (E11.5) and E17.5. The pregnant mice at E18.5 were utilized to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Pre-treatment with metformin significantly decreases urine microalbumin levels and serum β2-microglobulin in GDM mice during late pregnancy. Furthermore, GDM mice following metformin treatment have reduced serum levels of IL-6, TNF-α, and low phosphorylation of MAPK1/3, MAPK14, and MAPK8 in the kidneys (Liu et al, 2019). In addition, metformin treatment can protect diabetic nephropathy by improving glycoxidation, together with inhibition of fibrosis and inflammation in the kidneys of diabetic GK rats fed with an atherogenic diet.…”
Section: Kidney Diseasesmentioning
confidence: 99%
“…Pre-treatment with metformin significantly decreases urine microalbumin levels and serum β2-microglobulin in GDM mice during late pregnancy. Furthermore, GDM mice following metformin treatment have reduced serum levels of IL-6, TNF-α, and low phosphorylation of MAPK1/3, MAPK14, and MAPK8 in the kidneys (Liu et al, 2019). In addition, metformin treatment can protect diabetic nephropathy by improving glycoxidation, together with inhibition of fibrosis and inflammation in the kidneys of diabetic GK rats fed with an atherogenic diet.…”
Section: Kidney Diseasesmentioning
confidence: 99%
“…If the vaginal plug appeared the next morning, the mice were deemed to be pregnant for 0.5 days. The mice in the GDM group continued to be fed with HFD until embryonic day 18 [ 22 , 23 ]. For the GDM mice, on the 7.5-day of pregnancy, the blood glucose level in mouse tail vein blood was measured with the assistance of an Accu-Chek Performa glucose meter (Roche Diagnostics GmbH, Mannheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The injection volume of NPs was 200 µL/mouse (containing 2 µL of oligonucleotides [AMO], 50 µmol/L). Each mouse was given at 100 µL/mouse by tail vein (GenePharma) [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…A double-blind, placebo-controlled, parallel design study for rosiglitazone versus placebo groups with T2DM patients showed that serum creatinine concentration was similar in placebo, rosiglitazone, and metformin groups (18). However, a cross sectional observational study demonstrated that metformin use could enable reduction of creatinine levels and provided unique cardiac and renal protection (19).…”
Section: Chronic Kidney Disease and Metforminmentioning
confidence: 99%